PENGARUH INFLUENCER MARKETING RATING DAN KEMUDAHAN TRANSAKSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK SKINCARE WARDAH - Peptiana Peptiana; Ade Tiara Yulinda (UM. Bengkulu, 2026)
This study aims to analyze the influence of influencer marketing, product ratings, and transaction convenience on purchasing decisions for Wardah skincare products in Bengkulu City. With the rise of digital marketing, influencer-based promotions have become increasingly popular, while product ratings and transaction convenience also play a role in shaping consumer behavior in online shopping. This research employs a quantitative approach using a survey method, with data collected through questionnaires from 105 respondents who are Wardah consumers. Data analysis was conducted using multiple linear regression to examine the relationship between independent and dependent variables. The findings reveal that influencer marketing and transaction convenience significantly influence purchasing decisions, whereas product ratings do not have a significant effect. Partially, influencer marketing has the most dominant impact on consumer purchasing decisions, followed by transaction convenience. These findings highlight that marketing strategies involving credible influencers and seamless transaction processes can enhance consumer trust and purchasing decisions, even though product ratings are not a primary factor in consumer choices. Therefore, this study recommends that companies optimize their digital marketing strategies to increase product appeal and competitiveness in the market. Keywords: Influencer Marketing, Product Ratings, Transaction Convenience, Purchasing Decisions, Wardah Skincare.